Economic Production Lot Size Model with Stochastic Demand and Shortage Partial Backlogging Rate under Imperfect Quality Items - Kumar, Mukesh; Chauhan, Anand; Kumar, Pankaj (International Journal of Advanced Science and Technology, 2011)
In this paper we presents the EPLS (Economic Production Lot Size) model which accounts for a production system producing perfect and imperfect quality items. Also, a single period multi-item volume flexible production model for deteriorating items with stochastic demand and stochastic imperfect production. Deterioration is taken as constant. Linear holding cost is considered. Shortages are permitted in inventory with partial backlogging. Profit maximization techniques are also used. The problem parameter effects upon the optimal solutions are examined numerically.